A Review on the Challenges of Artificial Intelligence in HealthCare Systems in Rural Areas - Olugboja, Adedeji (European Journal of Applied Sciences, 2023)
This paper examines the challenges of implementing AI technology in rural healthcare systems. Despite the potential benefits of AI, rural healthcare systems face significant obstacles, including limited access to technology, a lack of resources, and a shortage of trained personnel. The essay argues that addressing these challenges is critical to ensure that rural communities have access to high-quality healthcare services. The solutions suggested include government funding, education and training programs, and partnerships with technology companies. By adopting these solutions, rural healthcare systems can harness the potential benefits of AI technology and improve patient outcomes. This paper concludes by suggesting directions for future research, including investigating additional solutions for overcoming the challenges of AI implementation in rural healthcare systems and exploring the long-term impact of AI technology on patient outcomes in rural areas.